The use of tax havens in exemption regimes - Anna Gumpert; James R. Hines Jr.; Monika Schnitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
This paper analyzes the tax haven investment behavior of multinational firms from a country that exempts foreign income from taxation. High foreign tax rates generally encourage firms to invest in tax havens, though significant costs of reallocating taxable income dampen these incentives. The behavior of German manufacturing firms from 2002-2008 is consistent with this prediction: at the mean, one percentage point higher foreign tax rates are associated with three percentage point greater likelihoods of owning tax haven affiliates. This contrasts with earlier evidence for U.S. firms subject to home country taxation, which are more likely to invest in tax havens if they face lower foreign tax rates. Foreign tax rates appear to be unrelated to tax haven investments of German firms in service industries, possibly reflecting the difficulty they face in reallocating taxable income.
urn:nbn:de:bvb:19-epub-13173-0
Keywords: H87; F23; 330; Tax Havens; Multinational Firms; Tax Avoidance; Profit Shifting; Manufacturing FDI; Service FDI; Steueroase; Multinationales Unternehmen; Steuervermeidung; International; Auslandsinvestition; Deutschland; USA; Welt